2017
DOI: 10.1159/000477977
|View full text |Cite
|
Sign up to set email alerts
|

Management of Helicobacter pylori Infection: What Should the Surgeon Know

Abstract: Infection with Helicobacter pylori continues to represent a major global health care burden, and various national and international consensus reports and guidelines have aimed at tracking recent developments for their translation into an optimized clinical management. The most important ‘innovation' is the definition of H. pylori gastritis as an infectious disease. This does imply the consideration of therapy of this condition even before the development of clinical manifestations including non-malignant and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…This study found out that Pronto dry rapid urease® out performed culture in sensitivity and NPV measures. This findings are in agreement with similar studies performed in elsewhere [12,13,14] Moreover, sensitivity of Pronto dry rapid urease® according to the manufacturer is similar with our findings [15]. The observed high sensitivity makes Pronto dry rapid urease® appropriate for screening ahead of the more time consuming confirmatory tests.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study found out that Pronto dry rapid urease® out performed culture in sensitivity and NPV measures. This findings are in agreement with similar studies performed in elsewhere [12,13,14] Moreover, sensitivity of Pronto dry rapid urease® according to the manufacturer is similar with our findings [15]. The observed high sensitivity makes Pronto dry rapid urease® appropriate for screening ahead of the more time consuming confirmatory tests.…”
Section: Discussionsupporting
confidence: 94%
“…It is possible some participants may have taken antibiotics and could not tell they were those in question. This culture findings are however not unique to this study, since even a study conducted by [18] had similar results. Culture is imperative for antimicrobial susceptibility profiling.…”
Section: Discussionsupporting
confidence: 46%
“…Helicobacter pylori (H. pylori) is a gram-negative, flagellated, microaerophilic bacterium that colonizes the human gastric mucosa (1) and causes chronic gastritis, peptic ulcer, and gastric cancer, as well as mucosa-associated lymphoid tissue (MALT) lymphoma. Recent studies have reported that H. pylori infection is an independent risk factor associated with unexplained iron-deficiency anemia and micronutrient deficiency (iron and vitamin B12) (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Neither of these diagnostic tools is considered to be the gold standard due to poor sensitivity or specificity. The choice of diagnostic test depends on the prevalence, age-related gastric cancer incidence in each area, accessibility, advantages and disadvantages of each method as well as different clinical circumstances of each patient [8] Aim of the study was to investigate association of Helicobacter pylori infection with endoscopic findings amongst dyspeptic patients at Aga Khan University Hospital.…”
Section: Introductionmentioning
confidence: 99%